Whole Earth Telescope observations of the pulsating subdwarf B star PG 0014+067 - Vuckovic, Maja (2006)
PG 0014+067 is one of the most promising pulsating subdwarf B stars for seismic analysis, as it has a rich pulsation spectrum. The richness of its pulsations, however, poses a fundamental challenge to understanding the pulsations of these stars, as the mode density is too complex to be explained only with radial and nonradial low-degree (l< 3) p-modes without rotational splittings. One proposed solution, suggested by Brassard et al. in 2001 for the case of PG 0014+067 in particular, assigns some modes with high degree (l=3). On the other hand, theoretical models of sdB stars suggest that they may retain rapidly rotating cores, and so the high mode density may result from the presence of a few rotationally split triplet (l = 1) and quintuplet (l = 2) modes, along with radial (l = 0) p-modes. To examine alternative theoretical models for these stars, we need better frequency resolution and denser longitude coverage. Therefore, we observed this star with the Whole Earth Telescope for two weeks in 2004 October. In this paper we report the results of Whole Earth Telescope observations of the pulsating subdwarf B star PG 0014+067.We find that the frequencies seen in PG 0014+067 do not appear to fit any theoretical model currently available; however, we find a simple empirical relation that is able to match all of the well-determined frequencies in this star.